IMPLEMENTATION OF BOGOR MAYOR REGULATION NUMBER 55 OF 2020 CONCERNING THE PRESERVATION OF SUNDA CULTURE - Tri Ramdani, Faisal; Apriliani, Afmi; Ilyanawati, Rd. Yuniar Anisa; Apriliyani, Neng Virly; Khaerunnisa; Ramadanti, Nisrina Putri; Pratami, Mirna (Jurnal Governansi, 2023)
The implementation of Bogor Mayor Regulation Number 55 of 2020 Concerning the Preservation of Sundanese Culture in Bogor City is discussed in this study with a focus on research locations focused on The Bogor City Culture, Tourism and Creative Economy Service. By successfully implementing this policy, it is hoped that Sundanese culture can be preserved and maintained as an ancestral way of life. This study employs a descriptive quantitative approach methodology, and the sampling strategy employed is outside purposive in selecting the sampling of 25 respondents who were drawn from staff members of the Office of Culture, Tourism, and Creative Economy of Bogor City. to obtain research results using calculations weight mean score (WMS) in order to determine the research results using the Slovin formula. The calculation results obtained were 3.90 with the GOOD category, which indicates that the implementation of Sundanese cultural preservation policies in Bogor City has been going well, according to the results of the recapitulation of the questionnaire calculation with the operationalization of variables based on Edward III’s theory of Successful Policy Implementation.